Dewatering of Kaoline Wastes by Flocculation - Kursun, Ilgin; G. Ozkan, Safak; Faruk Eskibalci, M.; Cinku, Kenan (Asian Journal of Chemistry, 2016)
Flocculation is an important sedimentation method for increasing dewatering efficiency. In this study, dewatering studies of fine grained kaoline obtained from feldspar processing plant waste at minus 20 μm in pulp was conducted to reveal flocculation properties.